Políticas públicas de proteção social a infância em situação de rua : uma análise das implicações de tendências na materialização das políticas públicas em Goiânia - Silva Netto, Valdir Nunes da (2023)
ABSTRACT: This dissertation aims to analyze public policies for social protection of homeless children in Goiânia/GO in light of contemporary inflections that permeate public actions and services aimed at this segment. The study sought to identify the origins and development of these public policies in the municipality of Goiânia/GO, with emphasis on possibleruptures or discontinuities in the actions of the municipal government in the period from 2017 to 2022. The epistemological basis that supports the development of thisstudy is the Dialectical and Historical Materialism and for the proproduction of data, bibliographic and documentaryresearch was used in books, magazines, theses, weekly journals, legislative diplomas, direct public administration websites, research institutions, social entities, and organizations. Based on the analysis and structuring of this dissertation, it was possible to understand the complexity of the issues surrounding homeless children, from the structural dimensions of inequalities in contemporary capitalist society to the historical evolution of child protection policies in Brazil.